Immunostimulatory activity of avocado oil in mice (Mus musculus) - Jusuf, Elena Adjani; Mustika, Aulia Andi; Andriyanto, Andriyanto (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2023)
Avocado fruit contains bioactive compounds that have the potential to act as an immunomodulator. This study aims to identify the ability of avocado oil as an immunomodulator based on the macrophage phagocytic activity and index of mice injected with nonpathogenic Staphylococcus aureus and to determine the most effective dose as an immunomodulator. This study used 30 male Deutschland Denken Yoken (DDY) mice, which were divided into five groups: placebo as negative control (mineral water), positive control (commercial immunomodulator containing Echinacea purpurea extract), and avocado oil 1 g/kg BW, 3 g/kg BW, and 5 g/kg BW. The treatment was carried out orally once a day for 14 days. Mice were induced by nonpathogenic Staphylococcus aureus on day 15 intraperitoneally, and after one hour, mice were euthanized to collect the peritoneal fluid. Peritoneal fluid smear preparations were made before active macrophages and phagocytosed Staphylococcus aureus were observed under a microscope. Phagocytic activity and phagocytic index were calculated. Avocado oil 5 g/kg BW showed the highest phagocytic activity and phagocytic index results with values of 71.00% ± 5.40% and 2.79 ± 0.14, respectively. Avocado oil enhances non-specific immune responses through macrophagephagocytic activity and index, demonstrating its immunostimulatory potential.